Kontribusi Rohani Islam (Rohis) Dalam Meningkatkan Kecintaan Kepada Al-Qur’an Di Sma Negeri 1 Medang Deras Batubara - Nur Kumala Sari; Mesran Mesran; Irwansyah Irwansyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This research is entitled “The Contribution of Islamic Spirituality Organization (ROHIS) in Increasing the Love for the Qur'an at SMA Negeri 1 Medang Deras Batubara.” The objectives of this study are to (1) identify the programs of the Islamic Spirituality Organization (ROHIS) implemented at SMA Negeri 1 Medang Deras Batubara, (2) explore the forms of students’ love for the Qur’an within the school environment, and (3) examine the supporting and inhibiting factors of ROHIS in enhancing the students’ love for the Qur’an. This study employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. The research subjects consist of the school principal, Islamic religion teacher, ROHIS supervisor, and ten active students. Data were analyzed through data reduction, data display, and conclusion drawing. The results show that the ROHIS programs are implemented routinely and systematically, including Qur’anic recitation (tadarus), memorization, tilawah training, tafsir studies, and young da’i coaching. Students’ love for the Qur’an is manifested in their habits of reading, memorizing, understanding, and applying Qur’anic values in daily life. Supporting factors in increasing students’ love for the Qur’an include institutional support, the role of teachers and mentors, and students’ intrinsic motivation. In contrast, inhibiting factors include tight academic schedules, lack of awareness among some students, and insufficient support from outside the school. In conclusion, ROHIS plays a significant role in fostering students’ religious attitudes, particularly in nurturing and enhancing their love for the Qur’an in a gradual and sustainable manner.